New insights into the fracture evolution and instability warning predication for fissure-contained hollow-cylinder granite with different hole diameter under multi-stage cyclic loads. (June 2022) - Wang, Yu; Han, Jianqiang; Xia, Yingjie; Long, Dayu
Highlights: The influence of the hole diameter on fracture and instability of fissure-contained rock was investigated. Volumetric deformation, hysteresis damping and energy dissipation were influenced by hole diameter. The instability early warning can be realized using the dissipated energy rate. Post-test CT scanning highlights fracture of rock bridge segment and the final instability pattern. Abstract: This work aims to investigate the fracture evolution and instability warning predication for the fissure-contained hollow-cylinder granite exposed to multi-stage cyclic loads. The influence of the hollow hole diameter on rock fracture was experimentally investigated in terms of deformation, hysteresis damping effects, energy conversion, and failure modes. The testing results show that the fracture of rock is impacted by the communication of the hole and fissure, and the fracture at the rock bridge segment leads to the final instability. The instability waring, i.e., obvious dilatancy initiation, was predicted using volumetric deformation, strain rate, hysteresis damping, and energy rate, it is suggested that an early warning can be realized from the dissipated energy rate. Rock damage is quantificationally characterized by the dissipated energy, and a damage evolution model is proposed that exhibits good performance to fit the testing data. A series of CT images highlight the fracture of rock bridge segment and good agreement was found between the energy evolution and failure patterns.